Patients’ perception of infection control in dentistry - Pradhan, Dilesh; Tuladhar, Sapna Laxmi; Adhikari, Ram Kumar (Journal of Kathmandu Medical College, 2023)
Background: Dentistry is a high-risk profession for infections due to exposure to contaminated materials like blood, saliva, and instruments. Both dental staff and patients can contract diseases via person-to-person contact or contaminated objects. Objectives: To assess patient perception of infection control practices in dentistry which will help in planning effective public health care delivery. Methods: A descriptive cross-sectional study was carried out in 170 patients visiting Kathmandu Medical College Teaching Hospital (KMCTH) over the period of three months (2022 June to 2022 August) for any form of dental treatment. Ethical approval was granted by Institutional Review Committee of KMCTH on 8th June 2021. Data obtained were entered and analysed using SPSS v.21. Results: Majority of the participants believed dentists should wear gloves (164, 96.7%), face masks (159, 93.8%), and eye goggles (105, 61.9%) while treating patients, and 152 (89.6%) of participants agreed that dentist should change gloves between patients. However, nearly half of the participants were not hesitant to receive treatment from the dentist not wearing gloves (82, 48.3%) and mask (86, 50.7%). In total, 119 (70.2%) agreed that it was possible to catch an infection during dental treatment and 121 (71.3%) did take interest in sterilisation of instruments but only 21 (12.3%) always asked their dentist about the method of sterilisation. Conclusion: Patients possess a strong awareness of the importance for infection control in dental practice, however, this study underscores the importance of implementing effective infection control measures in dental settings to ensure the safety and well-being of patients.